A First Large-Cohort Study of Personality-Trait Stability Over the 40 Years Between Elementary School and Midlife - Hampson, Sarah E. (2006)
This report provides some initial findings from an investigation of the relations between childhood Big Five personality traits assessed by elementary-school teachers and similar traits assessed 40 years later by self-reports at midlife. Our analyses are based on data from a relatively large and culturally diverse sample (N = 799) that was first assessed between 1959 and 1967 when the participants were children in Hawaii. Short-term (1-3 years) test retest reliabilities were lower (.22 -.53) within childhood when personality is developing than within adulthood (.70 -.79) when personality stability may be at its peak. Stability coefficients across the 40-year interval between the childhood assessment and two measures of adulthood personality were higher for Extraversion (e.g., .29) and Conscientiousness (e.g., .25) than for Openness (e.g., .16), Agreeableness (e.g., .08) and Neuroticism (e.g., .00). Construct continuity between childhood and adulthood was evaluated by canonical analysis and by structural-equation modeling and indicated continuity at both a broad, two-dimensional level and at the level of the Big Five. The findings are discussed in relation to Caspi, Roberts, and Shiner’s (2005) principles of rank-order personality stability.